The Cambridge companion to science and religion - Harrison, Peter, 1955- (Cambridge ; New York : Cambridge University Press, 2010)
"In recent years, the relations between science and religion have been the object of renewed attention. Developments in physics, biology and the neurosciences have reinvigorated discussions about the nature of life and ultimate reality. At the same time, the growth of anti-evolutionary and intelligent design movements has led many to the view that science and religion are necessarily in conflict. This book provides a comprehensive introduction to the relations between science and religion, with contributions from historians, philosophers, scientists and theologians. It explores the impact of religion on the origins and development of science, religious reactions to Darwinism, and the link between science and secularization. It also offers in-depth discussions of contemporary issues, with perspectives from cosmology, evolutionary biology, psychology, and bioethics. The volume is rounded out with philosophical reflections on the connections between atheism and science, the nature of scientific and religious knowledge, and divine action and human freedom"--
Historical interactions. The fate of science in patristic and medieval Christendom / David C. Lindberg -- Religion and the Scientific Revolution / John Henry -- Natural theology and the sciences / Jonathan R. Topham -- Religious reactions to Darwin / Jon H. Roberts -- Science and secularization / John Hedley Brooke -- Religion and contemporary science. Scientific creationism and intelligent design / Ronald L. Numbers -- Evolution and the inevitability of intelligent life / Simon Conway Morris -- God, physics and the Big Bang / William R. Stoeger -- Psychology and theology / Fraser Watts -- Science, bioethics and religion / John H. Evans -- Philosophical perspectives. Atheism, naturalism and science : three in one? / Michael Ruse -- Divine action, emergence and scientific explanation / Nancey Murphy -- Science, God and cosmic purpose / John Haught -- Ways of relating science and religion / Mikael Stenmark.
Includes bibliographical references (p. 296-302) and index.
Keywords: Religion and science